Cannabidiol, cannabinol and their combinations act as peripheral analgesics in a rat model of myofascial pain - Wong, Hayes; Cairns, Brian E. (Archives of oral biology, 2019)
•Cannabidiol and cannabinol alone and in combination reversed masseter muscle sensitization in a behavioral model of temporomandibular disorders.•Both cannabinoids decreased the mechanical sensitivity of masseter muscle afferent fibers.•Though not as effective as delta-9-tetrahydrocannabinol, these compounds do not cause psychotropic effects. This study investigated whether local intramuscular injection of non-psychoactive cannabinoids, cannabidiol (CBD), cannabinol (CBN), cannabichromene (CBC) and their combinations can decrease nerve growth factor (NGF)-induced masticatory muscle sensitization in female rats. In awake rats, changes in mechanical sensitivity induced by intramuscular injection of NGF and cannabinoids were measured by applying an electronic von Frey hair over the masseter muscle to measure the withdrawal response. The effect of CBD (5 mg/ml) and CBN (1 mg/ml) or their combinations CBD/CBN (1:1 mg/ml or 5:1 mg/ml) were assessed. To confirm a peripheral action, electrophysiological experiments were undertaken in anesthetized rats to examine whether intramuscular injections of CBD (5 mg/ml) and CBN (1 mg/ml) altered the mechanical threshold of masticatory muscle mechanoreceptors. In behavioral experiments, CBD (5 mg/ml) or CBN (1 mg/ml) decreased NGF-induced mechanical sensitization. Combinations of CBD/CBN induced a longer-lasting reduction of mechanical sensitization than either compound alone. No significant change in mechanical withdrawal threshold was observed in the contralateral masseter muscles and no impairment of motor function was found with the inverted screen test after any of the treatments. Consistent with behavioral results, CBD (5 mg/ml), CBN (1 mg/ml) and the combination of CBD/CBN (1:1 mg/ml) increased the mechanical threshold of masseter muscle mechanoreceptors. However, combining CBD/CBN (5:1 mg/ml) at a higher ratio reduced the duration of this effect. This may indicate an inhibitory effect of higher concentrations of CBD on CBN. These results suggest that peripheral application of these non-psychoactive cannabinoids may provide analgesic relief for chronic muscle pain disorders such as temporomandibular disorders and fibromyalgia without central side effects.